EVALUATING THE EFFECTIVENESS OF AI APPLICATIONS FOR VOCABULARY DEVELOPMENT AMONG STUDENTS WITH DIVERSE LEARNING STYLES (Лучшие интеллектуальные исследования, 2025)
Abstract: This study explores the impact of Artificial Intelligence (AI) applications on vocabulary acquisition among students with various learning styles. As vocabulary is foundational to language proficiency, identifying effective strategies for its development is critical. AI-powered tools offer personalized learning experiences that can adapt to students' preferences and cognitive styles. This research evaluates how these tools influence vocabulary growth among visual, auditory, reading/writing, and kinesthetic learners. Through a mixed-methods approach involving pre- and post-tests, user analytics, and interviews, the study demonstrates the positive influence of AI applications, particularly those that incorporate multimodal content and adaptive algorithms. Results suggest that tailoring AI applications to individual learning styles significantly enhances vocabulary acquisition.